KESEJAHTERAAN PSIKOLOGI DAN TEKANAN DALAM KALANGAN KAKITANGAN JABATAN ZAKAT DI MAJLIS AGAMA ISLAM NEGERI SEMBILAN (MAINS) - Abdullah, Nur Jannah; Aziz, Syazwana (Jurnal ’Ulwan, 2023)
This study was conducted to examine psychological well-being and stress among MAINS zakat department staff. Not only that, the objective of this study is to examine psychological well-being and gender and the difference between motivation and gender among zakat department staff at MAINS. A simple random sampling method was used to select 30 respondents in this study. The instruments used are Ryff Psychological Well-Being Scale (PWBS) and Depression, Anxiety and Stress Scale-21 (DASS-21). Questionnaires were distributed to respondents at the Zakat Department face-to-face. Descriptive statistical analysis was used to obtain the mean, medium, mode and standard deviation. Correlation analysis and t-test methods were used to test the research hypothesis. The data obtained was analyzed using the Statistical Package for Social Science (SPSS) version 26. The findings of the study show that there is no relationship between psychological well-being and stress among MAINS Zakat Department staff. The results of the study also show that there is no difference in psychological well-being and stress according to gender among the respondents. In conclusion, the findings of this study show that the stress factors faced by employees, whether male or female, do not affect psychological well-being at work.